Financial Confidence in Financial Satisfaction Through Financial Behavior for Ciputra School of Business Makassar Students - Aldrichnan Aprilio Chandra; Felysia Manggala; Richard Phurnama; Yuyun Karystin; Meilisa Suade; Nurfadilah Nurfadilah (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2022)
Financial literacy can lead to financial satisfaction (Henager & Anong, 2014). However, the majority of educated people are less content (Grable, J. E., Britt, S., & Cantrell, J., 2007). A person with greater financial literacy is more likely to excercise caution when making financial decisions and, therefore, less likely to feel confidence with their finances. This is also supported by studies by Hira, Fawslow, and Mugenda (cited in Robb & Woodyard, 2011). This study aims to empirically test the causal relationship of financial confidence and financial satisfaction use in relation to financial behavior. This study is an explanatory study aimed at discovering and explaining the causal relationship between variables (Sujarweni, 2019). The results of the study partially indicate a significant effect of financial satisfaction on financial behavior. Financial satisfaction has a positive relationship with financial behavior, Thus, it is concluded that hypothesis one is supported and tested by data (received) that financial satisfaction has a positive effect on financial behavior.